No difference in anti-spike antibody and surrogate viral neutralization following SARS-CoV-2 booster vaccination in persons with HIV compared to controls (CO-HIV Study) - Kling, Kendall D.; Janulis, Patrick; Demonbreun, Alexis R.; Sancilio, Amelia; Berzins, Baiba; Krueger, Karen; Achenbach, Chad; Price, Rachelle; Sullivan, Margaret; Caputo, Matthew; Hockney, Sara; Zembower, Teresa; et al. (Frontiers in Immunology, 2023)
Background: Understanding the immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination will enable accurate counseling and inform evolving vaccination strategies. Little is known about antibody response following booster vaccination in people living with HIV (PLWH). Methods: We enrolled SARS-CoV-2 vaccinated PLWH and controls without HIV in similar proportions based on age and comorbidities. Participants completed surveys on prior SARS-CoV-2 infection, vaccination, and comorbidities, and provided self-collected dried blood spots (DBS). Quantitative anti-spike IgG and surrogate viral neutralization assays targeted wild-type (WT), Delta, and Omicron variants. We also measured quantitative anti-nucleocapsid IgG. The analysis population had received full SARS-CoV-2 vaccination plus one booster dose. Bivariate analyses for continuous outcomes utilized Wilcoxon tests and multivariate analysis used linear models. Results: The analysis population comprised 140 PLWH and 75 controls with median age 58 and 55 years, males 95% and 43%, and DBS collection on 112 and 109 days after the last booster dose, respectively. Median CD4 count among PLWH was 760 cells/mm3 and 91% had an undetectable HIV-1 viral load. Considering WT, Delta, and Omicron variants, there was no significant difference in mean quantitative anti-spike IgG between PLWH (3.3, 2.9, 1.8) and controls (3.3, 2.9, 1.8), respectively (p-values=0. 771, 0.920, 0.708). Surrogate viral neutralization responses were similar in PLWH (1.0, 0.9, and 0.4) and controls (1.0, 0.9, 0.5), respectively (p-values=0.594, 0.436, 0.706). Conclusions: PLWH whose CD4 counts are well preserved and persons without HIV have similar anti-spike IgG antibody levels and viral neutralization responses after a single SARS-CoV-2 booster vaccination.